2000
DOI: 10.12968/jowc.2000.9.2.25954
|View full text |Cite
|
Sign up to set email alerts
|

A simple severity index for pressure ulcers

Abstract: The aim of this study was to design and test a pressure ulcer severity score based on assessment by experienced clinicians. Fifty pressure ulcers were each evaluated independently by seven experienced clinicians, using a scale that ranged from 0 (mildest damage) to 10 (most severe). Ulcer characteristics were analysed to determine which factors related to the assessments. A second set of 50 ulcers was used to test the validity of the resulting scoring system. Inter- and intra-observer reliability were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
6
0
3
Order By: Relevance
“…The dominant severity of the wounds in this study was grade 2 (35.7%) ( Table 2). The medians of DFUAS, BWAT, and PUSH at baseline were 26 (5-68), 38.5 , and 11 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), respectively.…”
Section: Characteristics Of Woundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant severity of the wounds in this study was grade 2 (35.7%) ( Table 2). The medians of DFUAS, BWAT, and PUSH at baseline were 26 (5-68), 38.5 , and 11 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), respectively.…”
Section: Characteristics Of Woundsmentioning
confidence: 99%
“…In 2008, Barber established the Barber measurement tool (BMT); Carlos and Soriano later developed the RESVECH V1.0 tool to measure chronic wounds . Tools for specific wound types include the Sessing scale (SS), the pressure ulcer scale for healing (PUSH), the pressure sore status tool (PSST), the wound healing scale (WHS), CODED, and DESIGN‐R . The leg ulcer measurement tool (LUMT) was developed for leg ulcers .…”
Section: Development Of the New Dfuasmentioning
confidence: 99%
“…En la literatura se han presentado diferentes escalas que abarcan múltiples características de la piel, evaluando su estado e integridad: el trabajo de Verhonick (25) en la escala observacional de UPP, la escala Sessing (26), la escala WHS (Wound healing Scale) (27), la herramienta de cicatrización de Sussman (28), la escala PSST (Pressure Sore Status Tool) (29), la escala PUSH (Pressure Ulcer Scale for Healing) (30), la escala DESIGN (31) y la escala CODED (32).…”
Section: Medidas Multidimensionales Existentes De Cicatrizaciónunclassified
“…Escala CODED Planteada por Emparanza y cols. (32) en 2000, es una escala española. Su desarrollo se llevó a cabo evaluando a 50 pacientes con UPP y contrastando la información con la puntuación independiente que realizaban siete expertos.…”
Section: Escala Designunclassified
“…Staging or grading scales as the National Pressure Ulcer Advisory Panel staging system, European Pressure Ulcer Advisory Panel scale and Stirling scale are not suitable because these classification systems were designed to rate the severity of a pressure ulcer and not its healing. 5,6 In 1997, it was concluded that no ideal instrument to measure pressure ulcer healing was available. 3,7 These and later reviews, however, described only part of available instruments or described instruments used for other kinds of wounds.…”
Section: Introductionmentioning
confidence: 99%